Spectral splitting of a stimulated Raman transition in a single molecule - Zirkelbach, Johannes; Gurlek, Burak; Mirzaei, Masoud; Shkarin, Alexey; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review Research, 2023)
The small cross-section of Raman scattering poses a great challenge for its direct study at the single-molecule level. By exploiting the high Franck-Condon factor of a common-mode resonance, choosing a large vibrational frequency difference in electronic ground and excited states and operating at T<2K, we succeed at driving a coherent stimulated Raman transition in individual molecules. We observe and model a spectral splitting that serves as a characteristic signature of the phenomenon at hand. Our study sets the ground for exploiting the intrinsic optomechanical degrees of freedom of molecules for applications in solid-state quantum optics and information processing.
CRIS-Team Scopus Importer:2024-12-16